Analysis of yeast resistance to lignocellulosic-derived inhibitors - Leung, Ka Kay (2015)
The rapid depletion of fossil fuel reserves and concurrent increase in global temperatures has resulted in global demand for the production of alternative environmentally friendly fuels. First-generation biofuels that utilise cash crops for the extraction of fermentable sugars currently exist, but are highly controversial due to socioeconomic and environmental reasons such as diverting food production or deforestation. Therefore, second-generation biofuels that utilise lignocellulosic waste materials are a more attractive prospect. In Europe, lignocellulosic biomass wastes such as wheat straw, display great potential for the production of alternative energy sources such as bioethanol for transportation. Conversion to this biofuel requires microorganisms that will effectively utilise the constituent sugars to produce a high yield of product. Saccharomyces cerevisiae (S. cerevisiae) strains possess the most desirable phenotypes for this objective. However, the components of wheat straw are difficult to break down, therefore pretreatment is required. Pretreatment methods vary but often utilise various chemicals that produce compounds that are inhibitory to yeast. This affects the efficiency of fermentations. The focus of this work is on formic acid and a synthetic media containing the main inhibitor compounds released during pre-treatment of steam exploded wheat straw. Six pair-wise F1 crosses between four distinct parental S. cerevisiae clean lineage populations have been generated previously by Cubillos et al., 2009. The 96 F1 progeny from each cross have been assayed for tolerance phenotypes in order to determine QTLs (Quantitative Trait Loci), which will enable us to map genes contributing to the multi-genic trait of inhibitor tolerance. Overall, three QTLs were identified for formic acid and five QTLs were identified from the synthetic inhibitor mix. Candidate genes were selected from the QTL analysis and were tested by performing reciprocal hemizygosity assays to determine which genes are responsible for inhibitor resistance to enable the development of yeast strains suitable for second-generation biofuel production.